Pivotal Role of Anterior Cingulate Cortex in Working Memory after Traumatic Brain Injury in Youth - Cazalis, Fabienne; Babikian, Talin; Giza, Christopher; Copeland, Sarah; Hovda, David; Asarnow, Robert F. (Frontiers in Neurology, 2011)
In this fMRI study, the functions of the anterior cingulate cortex (ACC) were studied in a group of adolescents who had sustained a moderate to severe traumatic brain injury (TBI). A spatial working memory task with varying working memory loads, representing experimental conditions of increasing difficulty, was administered. In a cross-sectional comparison between the patients and a matched control group, patients performed worse than Controls, showing longer reaction times and lower response accuracy on the spatial working memory task. Brain imaging findings suggest a possible double-dissociation: activity of the ACC in the TBI group, but not in the Control group, was associated with task difficulty; conversely, activity of the left sensorimotor cortex (lSMC) in the Control group, but not in the TBI group, was correlated with task difficulty. In addition to the main cross-sectional study, a longitudinal study of a group of adolescent patients with moderate to severe TBI was done using fMRI and the same spatial working memory task. The patient group was studied at two time-points: one time-point during the post-acute phase and one time-point 12 months later, during the chronic phase. Results indicated that patients’ behavioral performance improved over time, suggesting cognitive recovery. Brain imaging findings suggest that, over this 12-month period, patients recruited less of the ACC and more of the lSMC in response to increasing task difficulty. The role of ACC in executive functions following a moderate to severe brain injury in adolescence is discussed within the context of conflicting models of the ACC functions in the existing literature.